Discordant pathological diagnosis of non‐alcoholic fatty liver disease: A prospective multicenter study. Issue 3 (17th December 2019) - Kuwashiro, Takuya; Takahashi, Hirokazu; Hyogo, Hideyuki; Ogawa, Yuji; Imajo, Kento; Yoneda, Masato; Nakahara, Takashi; Oeda, Satoshi; Tanaka, Kenichi; Amano, Yuichiro; Ogawa, Shinji; Kawaguchi, Atsushi; et al.
Abstract : Background: Liver biopsy has been the standard procedure for diagnosing and evaluating the severity of non‐alcoholic fatty liver disease (NAFLD) and non‐alcoholic steatohepatitis (NASH); however, interobserver discordance remains a critical issue in its pathological diagnosis. Methods and Results: We examined the concordance rates of pathological scoring and diagnosis between pathologists at individual institutions (local diagnosis) and two central pathologists specialized in liver pathology (central diagnosis). A total of 150 patients with NAFLD underwent prospective liver biopsies. NAFLD activity score (NAS) and fibrosis stage were evaluated, and NASH was determined according to Matteoni's classification. NAS, scores for all NAS components, and fibrosis stage were diagnosed at a lower degree by central compared with local diagnosis. NASH was diagnosed in 34% of the patients according to central pathologists compared with 54% according to local pathologists ( P  < 0.001). The concordance rates for NAS, steatosis, inflammation, ballooning, fibrosis, and NASH diagnosis were 26.7, 62.7, 51.3, 48.7, 43.3, and 50.7%, respectively. The correlation coefficient between local and central diagnoses was the lowest for the scoring of ballooning ( ρ = 0.218). Conclusion: Concordance rates among pathologists for the evaluation of NAFLD are currently poor, and simple and reliable diagnostic and evaluation criteria are urgently needed to improve the clinical management of NAFLD patients. Abstract : We examined the concordance rates for pathological scoring and diagnosis of NAFLD between the pathologists The concordance rates for NAS, steatosis, inflammation, ballooning, fibrosis, and NASH diagnosis were 26.7%, 62.7%, 51.3%, 48.7%, 43.3%, and 50.7%, respectively. Concordance rates among pathologists for evaluation of NAFLD are currently poor, and simple and reliable diagnostic and evaluation criteria are urgently needed